Short recovery augments magnitude of muscle damage in high responders - Machado, M.; Willardson, J. M. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To examine serum creatine kinase (CK) activity after resistance exercise bouts with different rest intervals between sets and exercises in high responding (HR) and normal responding (NR) subjects.